2018
DOI: 10.1016/s2095-3119(18)61998-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Suaeda salsa SsNHX1 gene confers enhanced salt and drought tolerance to transgenic Zea mays

Abstract: Maize is one of the most important crops worldwide, but it suffers from salt stress when grown in saline-alkaline soil. There is therefore an urgent need to improve maize salt tolerance and crop yield. In this study, the SsNHX1 gene of Suaeda salsa, which encodes a vacuolar membrane Na + /H + antiporter, was transformed into the maize inbred line 18-599 by Agrobacterium-mediated transformation. Transgenic maize plants overexpressing the SsNHX1 gene showed less growth retardation when treated with an increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…More and more evidence supported that lncRNAs play significant roles in stress response [ 41 , 46 48 ]. Although some functional genes such as ZmNHX , ZmHTK , MIP , and SnRK2 have been proven to participate in the response to salt stress in plants [ 6 , 7 , 49 , 50 ], only a few lncRNAs have been reported to involve salinity stress at a whole transcriptome level. To reveal the salt responsive lncRNAs and the mechanism underlying salt tolerance in maize, we first identified lncRNAs from maize seedling root at different salt treatment stages and normal conditions using whole transcriptome sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more evidence supported that lncRNAs play significant roles in stress response [ 41 , 46 48 ]. Although some functional genes such as ZmNHX , ZmHTK , MIP , and SnRK2 have been proven to participate in the response to salt stress in plants [ 6 , 7 , 49 , 50 ], only a few lncRNAs have been reported to involve salinity stress at a whole transcriptome level. To reveal the salt responsive lncRNAs and the mechanism underlying salt tolerance in maize, we first identified lncRNAs from maize seedling root at different salt treatment stages and normal conditions using whole transcriptome sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…In maize, large numbers of protein-coding genes involved in salt stress have been reported in previous studies. Overexpression of the Suaeda salsa Na + /H + antiporter gene ( SsNHX1 ) in maize enhances the salt tolerance of the transgenic maize [ 6 ]. ZmSnRK2.11 is a potential negative regulator involved in maize salt stress, which is up-regulated by high salinity.…”
Section: Introductionmentioning
confidence: 99%
“…Several important Na + transporters such as NHXs, SOS1 and HKTs found in glycophytes as well as in some halophytes are known to mediate salt resistance in plants ( Horie et al, 2009 ; Yang et al, 2009 ; Mishra et al, 2014 ; Hamamoto et al, 2015 ; Ma et al, 2019 ; Al-Harrasi et al, 2020 ). Ectopic expression of some of these Na + transporters in specific targeted tissues or in whole plants have been reported to increase the salinity tolerance of plants ( Yang et al, 2009 ; Li et al, 2011 ; Mian et al, 2011 ; Gao et al, 2012 ; Huang et al, 2018 ; Zhang et al, 2019 ; Al-Harrasi et al, 2020 ), implying that improvement in detoxification mechanisms of Na + possibly is a typical approach to generate salt tolerant crops. In addition, maintenance of high K + /Na + ratio in shoots as wells as roots is essential for salinity tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Vacuolar NHX1 is a membrane protein that plays an important role in the exchange of Na + for H + across the vacuolar membrane, and the segregation of Na + into vacuoles [ 22 ]. It was found that the tonoplast NHX1 was upregulated in S. fruticosa , S. salsa , S. maritima , and S. corniculata after salt stress [ 15 , 17 , 23 , 24 ]. After the SsNHX1/SucNHX1 gene was transferred into rice, maize, and Arabidopsis thaliana , the salt tolerance of the transgenic plants was significantly improved [ 21 , 23 , 24 , 25 ].…”
Section: Ion Regulation and Compartmentationmentioning
confidence: 99%